The Importance of International Trade in Developing Countries - Hathi, Pradeep N. (Recent Research Reviews Journal, 2025)
International trade plays a vital role in the economic development of developing countries. It provides these nations with access to larger markets beyond their borders, enabling them to sell their goods and services to a global audience. This exposure not only increases revenue but also encourages local businesses to enhance their production capabilities and innovate. Furthermore, international trade facilitates the transfer of technology and knowledge, which can significantly boost productivity and efficiency in various sectors. Additionally, engaging in international trade helps developing countries diversify their economies, reducing dependence on a limited number of exports. This diversification is vital for economic stability, as it mitigates risks associated with price fluctuations and demand changes in specific markets. Moreover, trade can facilitate job creation, as the augmentation of production and export activities demands an expanded and more diversified workforce. Additionally, it allows access to essential resources, improves competitiveness by setting global standards, and encourages cultural exchange that enhances diplomatic relations. Also, the integration into the global economy through international trade promotes sustainable development, improves living standards, and contributes to poverty alleviation in developing countries.
Keywords: Trade policies; GDP; Foreign direct investment (FDI); Cultural exchange; and Market Exchange